2018
DOI: 10.1111/acem.13502
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta‐analysis of Ketamine as an Alternative to Opioids for Acute Pain in the Emergency Department

Abstract: Ketamine is noninferior to morphine for the control of acute pain, indicating that ketamine can be considered as an alternative to opioids for ED short-term pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 54 publications
(61 reference statements)
2
63
0
5
Order By: Relevance
“…In a similar vein, take‐home naloxone can be co‐prescribed to reduce the risk of overdose mortality . Evocative treatments, such as ketamine, have even begun to permeate into the emergency management of acute pain and may prevent the initiation of opioid prescribing .…”
mentioning
confidence: 99%
“…In a similar vein, take‐home naloxone can be co‐prescribed to reduce the risk of overdose mortality . Evocative treatments, such as ketamine, have even begun to permeate into the emergency management of acute pain and may prevent the initiation of opioid prescribing .…”
mentioning
confidence: 99%
“…Clinical data are consistent with analgesic benefits of NMDAR antagonists for neuropathic pain 1 , CRPS 1,8 , acute pain in the emergency room 15 , and a reduced requirement for opiods 4 .…”
Section: Introductionmentioning
confidence: 56%
“…The use of ketamine as an alternative for the acute exacerbation of chronic pain related to malignant disease was reviewed and ketamine although ketamine was effective, the authors concluded that more randomized controlled studies were needed [25]. A comprehensive systematic review and meta-analysis of randomized controlled trials compared intravenous opioid analgesics to low-dose ketamine for relief of acute pain in the emergency department and concluded that ketamine is not inferior to morphine and was a viable alternative to opioids in the emergency department [28]. A prospective, randomized, double-blind trial held in an emergency department for patients from the age of 18 -55 that suffered acute, moderate to severe, abdominal, flank and musculoskeletal pain found that sub-dissociative doses of ketamine were successful in treating pain in comparison to intravenous morphine with a confidence index of 95% and P < 0.05 denoting statistical significance [21].…”
Section: Comparison In the Reduction Of Acute Painmentioning
confidence: 99%
“…The need for opioids such as morphine may be reduced by 26% -60% when ketamine is used as an adjunct [30]. Non-severe adverse effects that need to be monitored and treated due to low dose ketamine include nausea, dizziness, drowsiness, vomiting, decreased oxygen saturation [19] [28]. Opioids such as morphine also have similar non-severe adverse effects [19] [28], but their use also worsens the opioid epidemic [2] [14].…”
Section: Considerations For Practitioners and Nursesmentioning
confidence: 99%